Using Nanomaterials as Excellent Immobilisation Layer for Biosensor Design - Azeez Olayiwola Idris; Seyi Philemon Akanji; Benjamin O. Orimolade; Foluke Omobola Grace Olorundare; Shohreh Azizi; Bhekie Mamba; Malik Maaza (Biosensors, 2023)
The endless development in nanotechnology has introduced new vitality in device fabrication including biosensor design for biomedical applications. With outstanding features like suitable biocompatibility, good electrical and thermal conductivity, wide surface area and catalytic activity, nanomaterials have been considered excellent and promising immobilisation candidates for the development of high-impact biosensors after they emerged. Owing to these reasons, the present review deals with the efficient use of nanomaterials as immobilisation candidates for biosensor fabrication. These include the implementation of carbon nanomaterials—graphene and its derivatives, carbon nanotubes, carbon nanoparticles, carbon nanodots—and MXenes, likewise their synergistic impact when merged with metal oxide nanomaterials. Furthermore, we also discuss the origin of the synthesis of some nanomaterials, the challenges associated with the use of those nanomaterials and the chemistry behind their incorporation with other materials for biosensor design. The last section covers the prospects for the development and application of the highlighted nanomaterials.